PENYUSUNAN STRATEGI DISASTER MANAGEMENT SEBAGAI MITIGASI RISIKO BENDUNGAN DALAM PENGELOLAAN WADUK DAN BENDUNGAN CIRATA - Mochammad Agustian; Danizy Frentakoza (TEKNISIA, 2017)
Cirata Dam was built in 1983 and has a capacity of 2 volumes billion cubic meters of water. With such capacity, the Cirata dam has a potential hazard and high risk in the event of dam failure. Therefore, disaster management is needed to minimize the impact that may occur. PT PJB BPWC as the dam manager has preventive and compiled plan for emergency response to disaster management in accordance with PUPR Ministerial Regulation No. 27 of 2017 which regulates the three pillars of dam security conception. Monitoring instruments installed on the body of the dam on a regular basis can inform condition of the dam body structure. Besides that, the readiness of infrastructure, facilities and infrastructure needed when handling disaster emergencies to affected areas and communities, such as evacuation routes, assembly points and early warning systems that are important supports in disaster risk mitigation. Stages in the implementation of emergency response are also prepared in the form of document on the contingency of failure of the Cirata dam. All of these programs are planning in the implementation of emergency response so as to minimize losses and casualties that may occur.